2013
DOI: 10.1002/job.1896
|View full text |Cite
|
Sign up to set email alerts
|

Learning disability and leadership: Becoming an effective leader

Abstract: This study investigates learning disability (LD) as an individual-differences variable predicting leadership emergence, role occupancy, and effectiveness. We hypothesize that individuals with LD are less likely to occupy leadership roles, and that informal group processes (leadership emergence) will mediate the relationship between LD and leadership role occupancy. We also hypothesized that, among leaders promoted and selected for leadership training, there would be a negative relationship between LD and effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 91 publications
(117 reference statements)
1
20
0
Order By: Relevance
“…This was further evident in their shared belief that disabled members of staff make as good, if not better, leaders (which supports the literature, e.g. Luria et al, 2014), due to their experiences of their condition and their understanding of personal difficulties of their staff: 'Disabled people make more enlightened decisions, are more inclusive by nature, they ignore smaller things to allow bigger things to happen'.…”
Section: Do They Consider Themselves To Be Leaders?supporting
confidence: 69%
“…This was further evident in their shared belief that disabled members of staff make as good, if not better, leaders (which supports the literature, e.g. Luria et al, 2014), due to their experiences of their condition and their understanding of personal difficulties of their staff: 'Disabled people make more enlightened decisions, are more inclusive by nature, they ignore smaller things to allow bigger things to happen'.…”
Section: Do They Consider Themselves To Be Leaders?supporting
confidence: 69%
“…Managers invest many resources (including time, money, and thought) in selecting and developing potential leaders (Schwartz, Bersin, & Pelster, 2014). Some use measures of leadership emergence in order to identify employees with leadership potential (Luria, Kalish, & Weinstein, 2014), and they may invest in training and promotion programs for those selected as potential leaders (Chan & Drasgow, 2001;Reilly, Dominick, & Gabriel, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Managers invest many resources (including time, money, and thought) in selecting and developing potential leaders (Schwartz, Bersin, & Pelster, ). Some use measures of leadership emergence in order to identify employees with leadership potential (Luria, Kalish, & Weinstein, ), and they may invest in training and promotion programs for those selected as potential leaders (Chan & Drasgow, ; Reilly, Dominick, & Gabriel, ). However, these efforts often operate under the common assumption, mentioned earlier, that leadership potential will consistently be identified in individuals who score high in prototypical leadership traits regardless of the group context.…”
Section: Introductionmentioning
confidence: 99%
“…Given accumulating research findings (e.g., Byrne et al, ; Luria, Kalish, & Weinstein, ) that leaders' psychological well‐being or disorder affects their leadership, organizations need to recognize the mental health of their leaders as an issue of importance for leadership quality and overall organizational functioning (Barling & Cloutier, ). Considering the current findings, this raises daunting policy and intervention dilemmas.…”
Section: Discussionmentioning
confidence: 99%
“…This raises a significant issue, as self‐identifying with any form of mental illness introduces the prospects of stigmatization. As an example of this with respect to leadership, Luria et al () showed that although there were no differences in effectiveness between leaders with and without a learning disability, employees with a learning disability were significantly less likely to attain a leadership position, raising the possibility of a bias against those with a learning disability and other forms of mental disorders.…”
Section: Discussionmentioning
confidence: 99%